A Unified Approach to Analysis of Body Condition in Green Toads - Lukas Landler; Stephan Burgstaller; Magdalena Spießberger; Andras Horvath; Zhivko Zhelev; Ivelin Mollov; Ulrich Sinsch; Johannes Nepita; Florian Schwabel; Wolfgang Kuhn; Christian Köbele; Heinz Sedlmeier; et al. (Diversity, 2022)
Body condition is increasingly used to assess the status of populations and as a proxy for individual fitness. A common, quick and non-invasive approach is to estimate condition from the relation between body length and mass. Among the methods developed for this purpose, the Scaled Mass Index (SMI) appears best suited for comparisons among populations. We assembled data from 17 populations of European green toads (Bufotes viridis) with the aim of devising a standard formula applicable for monitoring this species. The mean value of the exponents describing length–mass allometry in these samples was 3.0047. Hence, we propose using 3 as a scaling coefficient for calculating the SMI in green toads. From the contrast of SMI values for both sexes within populations, estimated with either the population-specific or the standard coefficient, we conclude that applying the standard formula not only facilitates comparisons among populations but may also help to avoid misinterpretation of variation within populations.